AGROWISATA KELAKAI DI PALANGKARAYA - Saskia, Syahna Saskia; Hadinata, Irwan Yudha (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2023)
Central Kalimantan is a province that has a lot of diverse characteristics, one of the characteristics of Central Kalimantan is the processed foods made from kelakai. There are many people who interested to this type of ferns. Beside that, there are also many manufacturers of the processed foods. However, not infrequently there are still many who don't know about kelakai as a characteristic of Central Kalimantan. Therefore, Kelakai Agrotourism in Palangkaraya is a form of solution to this problem, to introduce kelakai as a characteristic of Central Kalimantan and as a distribution platform for manufacturers of processed kelakai foods in order to further advance MSMEs, especially in Palangkaraya as the provincial capital of Central Kalimantan. To realize the design goals, this Agrotourism has two aspects of objectives, they are educative and participatory, as a form of providing knowledge to the community accompanied by concrete actions (participation). To realize the design with this goal, it is necessary to use the concept of Metaphor Architecture as an introduction and education through a form of adaptation. To realize this agrotourism design, an introduction is needed for the Palangkaraya area where most of the soil texture here is of peat soil type, which means it requires a special strategy for development. To solve this problem, the method that can be used is the Ecological Architecture approach. Ecological Architecture is an architectural approach that promotes environmental preservation without changing its original form.To combine the two principles above, this Agrotourism design uses the Metaphor-Ecological concept where this concept is a form of metaphoric architecture and ecological architecture that synergizes into a concept with visual and functional aspects as it's embodiment.